Fish Lipid against Prostate Cancer (PC-3) through Apoptosis and Cell Cycle Arrest. (7th February 2021) - Gupta, Pragya; Serajuddin, M.
Abstract: Anti-proliferative and apoptotic activities of different concentrations (10-50 μg/ml) of total lipid of the freshwater fish, Labeo rohita against human prostate cancer cells (PC3) were assessed using cells viability analysis by MTT assay, intracellular ROS generation and nuclear condensation. The cell cycle analysis for DNA content was performed by flow cytometry. The fish lipid was found to be effective which changed the characteristic morphology of PC3cells and also decreased their cells number. The fish lipid significantly induced the cell cycle arrest and level of ROS which caused apoptosis in PC3cells. The anti-proliferative and apoptotic roles of the fish lipid against the cells of prostate cancer may be helpful for the prevention and development of anticancer drug.